A new Pteroncola species (Bacillariophyceae) from the South Shetland Islands, Antarctica - Almandoz, Gaston Osvaldo (2013)
The marine araphid diatom Pteroncola carlinii sp. nov. from a coastal Antarctic environment was described based on light and scanning electron microscopy observations. The new species was found as solitary cells in the phytoplankton and epiphytic on green algal filaments or diatom chains. It was distinguished from P. inane, the only recognized species, primarily by a well developed sternum, a hyaline mantle, apical pore fields composed of three horizontal rows of pores, a single rimoportula per valve, and a lower striae density. Two morphotypes of P. carlinii were distinguished based upon the ultrastructure of alveolate (chambered) striae in external view. While most specimens presented striae formed by transapically elongated slits, others showed striae composed of a row of small areolae. A revised description of Pteroncola was provided as well as a comparison with related genera in the Fragilariaceae, such as Brandinia, Catacombas, Fragilaria, Fossula, Hyalosynedra, Staurosirella and Thalassioneis.